A question of responsibility : the Palmerston North Hospital Board and charitable relief, 1925-1938 : a research essay presented in partial fulfilment of the requirements for the degree of Bachelor of Arts with honours in History at Massey University - Dalley, Bronwyn (Massey University, 1985)
This research essay is an examination of the distribution and administration of outdoor charitable relief by the Palmerston North Hospital Board over the period 1925 to 1938. The intention of this is to test certain comments made by historians concerning the administration of outdoor relief in the pre-Welfare State era in New Zealand. By examining relief administration in Palmerston North this study will add to out understanding of social welfare in a period that has not been investigated extensively. [From Introduction]